Activation of n-pentane while prolonging HZSM-5 catalyst lifetime during its combined reaction with methanol or dimethyl ether - Cordero-Lanzac, Tomás; Martínez, Cristina; Aguayo, Andrés T.; Castaño, Pedro; Bilbao, Javier; Corma, Avelino (Elsevier, 2022)
This work explores the synergies during combined reactions of n-pentane (nC5) with oxygenates (methanol or dimethyl ether, OX). The experimental runs have been carried out in a packed bed reactor at 500 ºC, using a high silica HZSM-5 zeolite-based catalyst with different oxygenate-to-n-pentane (OX/nC5) ratios in the feed. A significant enhancement of the n-pentane conversion occurs for low OX/nC5 ratios in the feed (0.1- 0.25), especially when using dimethyl ether (DME). In addition, the presence of npentane reduces the rate of catalyst deactivation by coking during the conversion of oxygenates. These results have been explained on the grounds of a mechanistic interaction between the reactants: (1) the fast formation of methoxy and olefin intermediates from oxygenates, particularly from DME, could explain the promotion of n-pentane cracking, by facilitating the activation of the alkane by hydrogen transfer reactions; (2) the attenuation of deactivation during the conversion of oxygenates could be related to a lower extent of the arene cycle in the dual-cycle mechanism (limiting the polymethylbenzene formation). The analyses of used catalysts by means of temperatureprogrammed oxidation and confocal fluorescence microscopy have pointed out the higher reactivity of DME than that of methanol also for yielding coke structures.
https://openpolicyfinder.jisc.ac.uk/id/publication/16707?from=single_hit
Keywords: Catálisis; Hidrocarburos; Procesos químicos; Craqueo catalítico; MTO; Catalizadores; Zeolitas; Ingeniería química